Outcomes of pregnancy in simultaneous pancreas and kidney transplant recipients: A single‐center retrospective study. Issue 10 (3rd August 2021) - Punjala, Sai Rithin; Phillips, Benedict Lyle; Chowdhury, Paramit; Pile, Taryn; Karydis, Nikolaos; Kessaris, Nicos; Olsburgh, Jonathon; Harding, Kate; Callaghan, Chris J.; Nelson‐Piercy, Catherine; Drage, Martin
Abstract: Simultaneous pancreas and kidney (SPK) transplantation, in uremic women with insulin‐dependent diabetes, increases the chance of a successful pregnancy and minimizes the risk to infants. The aim of this study was to document pregnancy and explore the challenges in this cohort of women. Retrospective analysis of women who underwent pancreas transplantation between January 1, 1998 and 8 January, 2019 was conducted. Seventeen pregnancies were identified in 13 women. Mean transplant‐to‐pregnancy interval was 4.6 years (range, 1.1–10.2 years). Eleven pregnancies resulted in live birth (65%), and six (35%) ended in miscarriage/fetal loss at a median gestational age of 8.5 weeks. Mean gestational age at delivery was 34.9 weeks (SD ±3 weeks). Preeclampsia and C‐section rates were 77% and 67%, respectively. Adverse fetal and graft outcomes were observed in 100% of unplanned pregnancies, compared to 10% of planned pregnancies ( P  < .001). One kidney allograft was lost during pregnancy; one pancreas and two kidney allografts were lost within 3 years of pregnancy. This is a high‐risk group for grafts and offspring. Pre‐pregnancy planning is vital. A multidisciplinary approach by obstetric and transplant teams is important pre‐pregnancy, antenatally, and peripartum. This is the largest published series of pregnancies in SPK recipients from a single center.